Cultural Differences and the Development of the IPMA-HR Competency Model in China during Its Economic Transitional Period - Sun (Linda) Li (Adult Education Research Conference, 2008)
This qualitative inquiry research uses the case study methodology within a constructivist conceptual framework. This study explores cultural differences and the development and implementation in China of a human resources competency model, the IPAM-HR competency certification training program, and analyzes the dynamics of the Chinese understanding of the competency model.
Keywords: competency model; training program; HR; China